Confirmation of occurrence of Trechus Clairville, 1806 in the Baltic amber forests, with description of a flightless edaphic species, and remarks on Trechoides Motschulsky, 1856 (Coleoptera: Carabidae: Trechini) - Schmidt, Joachim; Faille, Arnaud (Zootaxa, 2015)
The first reliably identified Trechini beetle species from Baltic amber, Trechus balticus sp. n., is described. This new fossil species is most similar to extant species of the Palaearctic Trechus sensu stricto, as well as to the Nearctic Microtrechus Jeannel, 1927. Since the fossil specimen is a female and some important character states cannot be investigated, its true systematic position within the genus Trechus sensu lato remains open. Trechoides fasciatus Motschulsky, 1856 is another fossil species that perhaps belongs to the Trechini clade. However, since the original description does not present any character of systematic value and, because the type is very probably lost, the true systematic position of this taxon remains unknown.